Interventional Approaches in VTE Treatment (Vena Cava Filters, Catheter-Guided Thrombolysis, Thrombosuction) - Imberti, Davide; Maraldi, Cinzia; Gallerani, Massimo (Seminars in Respiratory and Critical Care Medicine, 2012)
Venous thromboembolism (VTE), including deep vein thrombosis (DVT) and pulmonary embolism (PE), is the third most common cardiovascular pathology after coronary disease and cerebrovascular diseases and is responsible for significant morbidity and mortality in the general population. Full-dose anticoagulation is the standard therapy for VTE, both the acute phase and the prolonged treatment. The latest guidelines of the American College of Chest Physicians recommend treatment with a full-dose of unfractionated heparin (UFH), low-molecular-weight-heparin (LMWH), fondaparinux, vitamin K antagonist (VKA), or systemically administered thrombolytics for most of the patients with objectively confirmed VTE. Catheter-guided thrombolysis and thrombosuction are interventional approaches that should be used only in selected populations; interruption of the inferior vena cava (IVC) with a filter can be performed to prevent life-threatening PE in patients with VTE and contraindications to anticoagulant treatment, bleeding complications during antithrombotic treatment, or VTE recurrences, despite optimal anticoagulation. This review summarizes the currently available literature regarding interventional approaches in VTE treatment (vena cava filters, catheter-guided thrombolysis, thrombosuction), discusses their efficacy and safety, and reviews the appropriate indications for their use in daily clinical practice.
Keywords: venous thrombosis; vena cava filters; catheter-guided thrombolysis; thrombosuction